The association between diabetes‐related distress and fear of hypoglycaemia in patients with type 2 diabetes mellitus: A cross‐sectional descriptive study - Shuang Li; Li Fang; Amanda Lee; Mark Hayter; Lu Zhang; Yaxin Bi; Xiaxin Wu; Lin Liu; Hong Zhang; Yuan Yuan; Weijuan Gong; Yu Zhang (Nursing Open, 2021)
Abstract Aim The study aimed to explore the association between diabetes‐related distress as a dependent variable and fear of hypoglycaemia as a independent variable in Chinese individuals with type 2 diabetes, which can provide a basis for the development of effective nursing interventions. Design A cross‐sectional descriptive study. Methods Pre‐piloted scales were used to determine whether they experienced fear of hypoglycaemia and whether this impacted upon their management of the disease. From June–October 2019, participants were asked to complete the “hypoglycaemia fear survey” and “diabetes distress scales” to assess levels of fear and distress. Stepwise multivariate regression analysis was applied to reveal relationship between distress as a dependent variable and fear as a independent variable. Covariates included demographic, clinical or lifestyle factors. Results A total of 258 participants were recruited for the survey, and they were characterized by little or no distress (39.53%), moderate distress (45.35%) and high distress (15.12%). The prevalence of moderate to severe distress in patients was 60.47%. Increased diabetes‐related distress was strongly correlated with increased fear of hypoglycaemia and closely associated with the scores of the worry and behaviour subscales. These results indicated that 62.3% of diabetes‐related distress may be explained by fear of hypoglycaemia. Conclusion Increased diabetes‐related distress is associated with increased fear of hypoglycaemia in individuals with type 2 diabetes.